Lactobacillus paracasei F19 versus placebo for the prevention of proton pump inhibitor-induced bowel symptoms: A randomized clinical trial. Issue 4 (April 2015) - Compare, Debora; Rocco, Alba; Sgamato, Costantino; Coccoli, Pietro; Campo, Salvatore Maria Antonio; Nazionale, Immacolata; Larussa, Tiziana; Luzza, Francesco; Chiodini, Paolo; Nardone, Gerardo
Abstract Background Proton pump inhibitors may foster intestinal dysbiosis and related bowel symptoms. Aim To evaluate the effect of Lactobacillus paracasei F19 on bowel symptom onset in patients on long-term proton pump inhibitors. Methods In this randomized, double-blind, placebo-controlled study, patients with typical gastroesophageal reflux disease symptoms receiving pantoprazole 40 mg/d for six months were randomly assigned to receive: (A) Lactobacillus paracasei F19 bid for three days/week for six months; (B) placebo bid for three days/week for six months; (C) Lactobacillus paracasei F19 bid for three days/week for three months and placebo bid for three days/week for the following three months; (D) placebo bid for three days/week for three months and Lactobacillus paracasei F19 bid for three days/week for the following three months. Bloating, flatulence, abdominal pain and bowel habit were assessed monthly. Results 100/312 patients were enrolled. In the parallel groups, the treatment-by-time interaction affected bloating (p = 0.015), while Lactobacillus paracasei F19 treatment alone affected flatulence (p = 0.011). Moreover, the treatment-by-time interaction significantly affected the mean score of bloating (p = 0.01) and flatulence (p < 0.0001), the mean stool form (p = 0.03) and mean stool frequency/week (p = 0.016). Analysis of the cross-over groups, limited to the first three months because of carry-over effect, confirmed these results. Conclusion Lactobacillus paracasei F19 supplementation prevents bowel symptom onset in patients on long-term proton pump inhibitors.